Efeito da radiação ionizante, simulando radioterapia, nas propriedades de cerâmicas Y-TZP e cimentos resinosos - Silva, Pollyanna Nogueira Ferreira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study were to evaluate the effect of different types of washes and exposure to ionizing radiation (gamma rays), used in cancer treatments, the flexural strength of 4 points, crystalline phase transformation and color change of the polycrystalline ceramic Y- TZP; and the influence of gamma radiation on resistance to bending mini-resin cements protected with Y-TZP. 114 bars stabilized zirconia were made partially yttria - Cercon®Zirconia (DENTSPLY Ceramco, USA) and InCeram in 2000 YZ cubes (Vita Zahnfabrik, Germany) according to ISO 6872 (21 mm long x 4.5 mm wide x 1 2 mm thick) and 96 bars to mini-bending U200 RelyX (3M, Germany) and RelyX ARC (3M, Germany), divided according to the protective ceramic. Half of the samples Y-TZP and 64 samples of the cements were irradiated with 60Co gamma, in a single step of 70 Gy. Was held the flexural strength test in a universal testing machine (1 mm / min 1000 kg) and the mini-bending test (0,5 mm / min and 50 kg) and color change of the Y-TZP was used CIELAB system using the Compact® Easyshade (Vita Zahnfabrik, Germany). The strength data (MPa) and color data were submitted to the ANOVA and Tukey's test, both with α = 0.05. Part of the Y-TZP samples (n = 3) underwent-ray diffraction (XRD) for quantification of crystalline phases and scanning electron microscopy (SEM) to analysis of surface topography, while a sample from each group cement was subjected to infrared analysis (FTIR). The ceramic (p = 0.00), the type of wash (p = 0.02) and radiation (p = 0.01) and showed significant up, as well as interactions. For flexural strength of 4 points observed the largest value for the YZ washing with isopropyl alcohol and exposure to ionizing radiation (1200.7 ± 166.2 MPa). For staining, the ceramic parameters (p = 0.00) and wash (p = 0.00), as well as ceramics and washing interaction (p = 0.00) significantly influenced ΔE, ΔL, Δa and...

Os objetivos deste estudo foram avaliar o efeito de diferentes tipos de lavagens e exposição à radiação ionizante (raios gama), utilizada em tratamentos oncológicos, na resistência à flexão de 4 pontos, transformação de fase cristalina e alteração de cor da cerâmica policristalina de Y-TZP; e verificar a influência da radiação gama na resistência à miniflexão de cimentos resinosos cimentados com Y-TZP.Foram confeccionadas 114 barras de zircôniaestabilizada parcialmente por ítria - Cercon®Zirconia (DENTSPLY Ceramco, EUA) e InCeram 2000 YZ cubes (Vita Zahnfabrik, Alemanha) segundo a norma ISO 6872 (21 mm de comprimento x 4,5mm de largura x 1,2mm de espessura) e 96 barras para mini-flexão de RelyX U200 (3M, Alemanha) e RelyX ARC (3M, Alemanha), divididos de acordo com a cerâmica de proteção. Metade das amostras de Y-TZP e 64 amostras dos cimentos foram irradiadas com gama 60Co, em etapa única de 70 Gy. Foi realizado o teste de resistência à flexão em máquina de ensaio universal (1 mm/min, 1000kg) e para o teste de mini-flexão (0,5 mm/min e 50 kg) e para alteração de cor das Y-TZP foi utilizado o sistema CieLab com o uso do Easyshade Compact® (Vita Zahnfabrik, Alemanha). Os dados de resistência (MPa) e os dados da cor foram submetidos a à análise de variância e ao teste de Tukey, ambos com α=0,05. Parte das amostras de Y-TZP (n=3) foram submetidas à difração de raio-X (DRX) para quantificação das fases cristalinas e à microscopia eletrônica de varredura (MEV) para análise da topografia superficial, enquanto uma amostra de cada grupo de cimentos foi submetido à análise de infravermelho (FTIR). A cerâmica (p=0,00), o tipo de lavagem (p=0,02) e a radiação (p=0,01) mostraram-se significantes, assim como as interações. Para resistência à flexão de 4 pontos, observou o maior valor para a YZ com lavagem em álcool isopropílico com exposição á radiação ionizante....
Keywords: Zircônio; Raios X - Difração; Resistencia de materiais; Cimentos de resina